Revitalizing the science of the soul: psychology from an Islamic perspective - Bachelor of Human Sciences in Psychology (Honors), Department of Psychology, International Islamic University Malaysia, Kuala Lumpur, Malaysia - Abdul Khaiyom, Jamilah Hanum; Harun, Mohd Ferdaus; Jaffer, Usman; Fauzaman, Jusmawati; Abdul Rahman, Shukran (Department of Psychology, Riphah International Islamic University, Islamabad, Pakistan, 2025)
This paper presents an overview of the Bachelor of Human Sciences in Psychology (Honours) programme at the International Islamic University Malaysia (IIUM), highlighting its distinctive integration of contemporary psychological science with perspectives grounded in the Islamic intellectual tradition. Guided by the Tawhidic paradigm, the programme seeks to harmonise empirical inquiry with the “Science of the Soul” (‘Ilm al-Nafs), offering a holistic framework for understanding human behaviour and mental processes. The curriculum emphasises foundational psychological knowledge, technical competencies, and the integration of ethical and spiritual dimensions in teaching, research, and practice.